Integrasi Perspektif Feminisme dalam Kebijakan Publik: Tantangan Budaya Lokal terhadap Perlindungan Perempuan - Hazariga, Adam; Paini, Paini; Azrin, Nikmatul (Universitas Medan Area, 2025)
The protection of women is a crucial component in achieving gender justice within a state governed by law. However, public policy formulation often faces challenges from patriarchal local cultural values. This study aims to analyze the integration of feminist perspectives into public policy and the obstacles posed by customary norms. Using a qualitative descriptive method with a conceptual and statutory approach, the research draws on relevant legal literature and Indonesian policy documents. The findings indicate that despite the existence of progressive regulations, such as the Law on Sexual Violence Crimes (UU TPKS), their implementation is often hindered by conservative interpretations rooted in customary law. A feminist jurisprudence approach is essential to uncover gender disparities in legal practices. The study concludes that synergy between statutory law and gender-sensitive local wisdom is necessary to develop more inclusive and effective public policies.